Modern Technologies of Strategic HR Management in the Conditions of Innovative Development of Entrepreneurial Structures - I. V. Novikova; Z. K. Samaybekova (Управленческое консультирование, 2024)
In an era of rapid change and the introduction of new technologies, effective personnel management is becoming a key element in the successful development of business structures, and innovative technologies are becoming an integral part in strategic personnel management, optimizing current management processes and creating adaptive, high-performance and innovation-oriented teams. They help companies not only attract, develop and retain talent, but also create innovative corporate cultures capable of continuous growth and transformation. The purpose of researching innovative technologies in strategic personnel management is related to identifying the potential of innovative technologies to improve business processes, increase efficiency, create a favorable environment for employees and ways of their optimal implementation to achieve strategic goals in business structures. The article proposes an interpretation of the concept of “innovative technologies in strategic personnel management”. The methods of finding work for unemployed citizens in the Kyrgyz Republic for the period 2012–2021 are analyzed. Innovative technologies in strategic personnel management are considered, such as business process automation, artificial intelligence, cloud HR platforms, learning management systems, gamification and virtual reality, communication platforms that open up new prospects for creating progressive and flexible work environments. The advantages and disadvantages of introducing innovative technologies in strategic personnel management in the conditions of innovative development of business structures are highlighted. It is noted that the choice of innovative technologies should be based on the resources available in the business structure and the basic tasks of the strategic personnel management system. A combination of technologies is recommended that collectively increase the effectiveness of the strategic personnel management system in innovative development.